2015
DOI: 10.1016/j.ajog.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy induces persistent changes in vascular compliance in primiparous women

Abstract: Objective Pregnancy induces rapid, progressive and substantial changes to the cardiovascular system. The low recurrence risk of preeclampsia, despite familial predisposition, suggests an adaptation associated with pregnancy that attenuates risk for subsequent preeclampsia. We aimed to evaluate the persistent effect of pregnancy on maternal cardiovascular physiology. Study Design Forty-five healthy nulliparous women underwent baseline cardiovascular assessment preconception and repeated an average of 30 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 30 publications
3
58
0
4
Order By: Relevance
“…Within the extended postpartum period,  increases modestly above non-pregnant values 11. Previous studies have reported prolonged effects on cardiovascular function following gestation, including increased arterial compliance 42. In the late postpartum, SVR is reduced below non-pregnant and early postpartum levels.…”
Section: Discussionmentioning
confidence: 89%
“…Within the extended postpartum period,  increases modestly above non-pregnant values 11. Previous studies have reported prolonged effects on cardiovascular function following gestation, including increased arterial compliance 42. In the late postpartum, SVR is reduced below non-pregnant and early postpartum levels.…”
Section: Discussionmentioning
confidence: 89%
“…From about the fifth week of gestation, pregnancy induces rapid, progressive and substantial alterations to the cardiovascular system,51 which ensure blood supply to the fetus 52. Oestrogen-mediated remodelling reduces vascular tone, leading to a primary reduction in afterload and an increase in venous capacitance 51.…”
Section: Pregnancymentioning
confidence: 99%
“…2,3 Both systemic and uterine vascular resistances are decreased, 4,5 due to vasodilation in mesenteric 6 and uterine circulations, [6][7][8] and this enhances blood flow to the uterus. In addition, pregnancy induces changes in structural parameters such as distensibility in the uterine vessels 5 and stiffness in the systemic vasculature, [9][10][11] among other important modifications of vascular response.…”
Section: Introductionmentioning
confidence: 99%
“…However, some degree of pregnancy-induced vascular adaptation continues PP 9,12-14 and includes increased cardiac output, decreased peripheral vascular resistance, 13 and changes in vascular compliance 9 and is regulated by molecules such as nitric oxide (NO) 15 and by changes in cardiac structure and function. 16,17 Moreover, PP systemic vasculature may exhibit new remodeling, such as outward remodeling of mesenteric resistance arteries, 12 which may result in the redistribution of the cardiac output systemically as blood flow to the uterus decreases to approximate the prepregnancy condition.…”
Section: Introductionmentioning
confidence: 99%